Measurement Model of Professional Learning Community: A Malaysian Teacher Context - MOHD FAIZ MOHD YAAKOB (Indonesian Research Journal in Education |IRJE|, 2017)
The main purpose of the study was to develop an empirical empirically measurement model for Professional Learning Community (PLC) among teachers in Malaysia primary schools. Structural Equation Modelling (SEM) utilizing AMOS Version 22 was employed to develop the model. Exploratory Factor Analysis (EFA) was utilized to identify the underlying factors, whereas confirmatory factor analysis was employed to test the construct of the PLC. The study involved 450 primary school teachers from 5 zones in Malaysia represented by the states of Kedah, Selangor, Johor, Terengganu and Sarawak. Professional Learning Community Model (PLC) was found to be fit and reliable model with all fit statistics set well above the threshold level. The finding has also encouraged a fresh look at the implementation of PLC program aimed at successful change in schools. The findings of the PLC will also benefit educational practitioners in designing a teacher professional development.